BALB/c mice infected with antimony treatment refractory isolate of Leishmania braziliensis present severe lesions due to IL-4 production. - Diego L Costa; Vanessa Carregaro; Djalma S Lima-Júnior; Neide M Silva; Cristiane M Milanezi; Cristina R Cardoso; Ângela Giudice; Amélia R de Jesus; Edgar M Carvalho; Roque P Almeida; João S Silva (PLoS Neglected Tropical Diseases, 2011)
BACKGROUND: Leishmania braziliensis is the main causative agent of cutaneous leishmaniasis in Brazil. Protection against infection is related to development of Th1 responses, but the mechanisms that mediate susceptibility are still poorly understood. Murine models have been the most important tools in understanding the immunopathogenesis of L. major infection and have shown that Th2 responses favor parasite survival. In contrast, L. braziliensis-infected mice develop strong Th1 responses and easily resolve the infection, thus making the study of factors affecting susceptibility to this parasite difficult. METHODOLOGY/PRINCIPAL FINDINGS: Here, we describe an experimental model for the evaluation of the mechanisms mediating susceptibility to L. braziliensis infection. BALB/c mice were inoculated with stationary phase promastigotes of L. braziliensis, isolates LTCP393(R) and LTCP15171(S), which are resistant and susceptible to antimony and nitric oxide (NO), respectively. Mice inoculated with LTCP393(R) presented larger lesions that healed more slowly and contained higher parasite loads than lesions caused by LTCP15171(S). Inflammatory infiltrates in the lesions and production of IFN-γ, TNF-α, IL-10 and TGF-β were similar in mice inoculated with either isolate, indicating that these factors did not contribute to the different disease manifestations observed. In contrast, IL-4 production was strongly increased in LTCP393(R)-inoculated animals and also arginase I (Arg I) expression. Moreover, anti-IL-4 monoclonal antibody (mAb) treatment resulted in decreased lesion thickness and parasite burden in animals inoculated with LTCP393(R), but not in those inoculated with LTCP15171(S). CONCLUSION/SIGNIFICANCE: We conclude that the ability of L. braziliensis isolates to induce Th2 responses affects the susceptibility to infection with these isolates and contributes to the increased virulence and severity of disease associated with them. Since these data reflect what happens in human infection, this model could be useful to ...